KEDUDUKAN ANAK AKIBAT PEMBATALAN PERKAWINAN DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Fuad Buchari; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The phenomenon of marriage's cancellation often happenned in Indonesian society today. When a marriage does not fulfill the terms marriage, then the marriage can be canceled. With the result of the marriage's cancellation its means consider the marriage was breaking up and never happened. As a result, there are some aggrieved party as a child. Law No. 1 Year 1974 About Marriage and Government Regulation No. 9 of 1975 does not regulate in detail the position of the child if both parents marriage was canceled. While between children and parents have strong legal relationship, including in terms of inheritance and guardianship. In Article 42 of Law No. 1 of 1974 concerning marriages mentioned that the legitimate child is the child who born in or out of marriage as valid, while valid marriage is a marriage that qualifies validity of marriage.